The politics of ritual change: the "zukru" festival in the political history of late Bronze Age Emar - Thames, John Tracy (Harvard Semitic monographs, 2020)
Contents -- Preface and Acknowledgements -- List of Abbreviations -- List of Abbreviations for Texts from Emar and its Vicinity -- List of Tables -- part 1: The City of Emar and Its zukru Rituals -- 1 Introduction to the City of Emar -- 1 Archaeological Excavations at Tell Meskeneh -- 2 The Archives of Emar -- 3 Emar’s Scribal Distinctions -- 2 The zukru Ritual: The City’s Offering to Dagan -- 1 Texts and Translations: Emar 375+ 397 + 401 + 428 + 448* + 449* -- 2 The zukru Ritual of the City of Emar -- 3 Gods and Men in the zukru Ritual -- 4 The Performance of the zukru Ritual -- 3 The zukru Festival: Expansion of Local Traditions -- 1 Texts and Translations: Emar 373 + 374 + 376 + 424 + 425 + Dercksen Kaskal No. 3 -- 2 Textual and Philological Notes -- 3 The zukru Ritual in its Festival Version -- 4 zukru Festival Divinity -- 5 The Ritual Transaction: Donations to the Gods -- 6 The Sponsors of the zukru Festival -- 7 The Provisioning of the zukru Festival -- 8 The Performance of the zukru in Its Festival Form -- 4 Part 1 Conclusion: The zukru Traditions -- 1 The Meaning of the Word “zukru” -- 2 The zukru Rituals: A Synthetic View -- part 2: Politics and Rituals -- 5 Emar in the Late Bronze Age: History, Politics, and Chronology -- 1 The Question of Emar’s Relationship to Mittani -- 2 Local Politics of Emar: The Conventional Format Documentation -- 3 The Hittite Conquest of North Syria -- 4 The Role of Hittite Karkamiš in Emar Politics: Evidence of the Free Format Documentation -- 5 The Relationship between Local and Foreign Authorities: Chronological Considerations and Political Change -- 6 Politics, Power, and the zukru Festival -- 1 The King and the zukru Festival -- 2 zukru Practice under Hittite Aegis -- 3 Hittite Involvement in Emar’s Cults -- 4 Cults of Anatolian Deities at Emar -- 5 The Hittite Interest in Emar’s Cults -- 6 Historical Context and the Dating of the zukru Texts -- 7 Conclusion: Power, Politics, and Change in the zukru Rituals -- Bibliography -- Index of Ancient Texts -- Index of Authors.